(untitled) (Al-Qamar, 2018)
Spoken words leave its impression in human daily life and play an important role to change the conversation trends from harshness to softness. The present paper discusses kindness in Arab approaches. It finds that individual courtesy and group positions are two main baptized positions of the speaker which have been elaborated with some examples. Politeness, respect and modesty, optimism, pessimism, veneration and glorification are the main motives of kindness in Arab styles، which have been illustrated to enrich the study. This research paper is a motivational study to use the soft and kind words in daily conversation which will lead to kindness, softness and caring attitude in human society.